2019
DOI: 10.1039/c9ob00510b
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of cyanoformamides via a CsF-promoted decyanation/oxidation cascade of 2-dialkylamino-malononitriles

Abstract: The synthesis of cyanoformamides via a CsF-promoted decyanation/oxidation cascade of N,N-disubstituted aminomalononitriles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…Recently, other more direct synthetic methods have been developed (Scheme 2). 23–29 For instance, Muñoz reported that the reaction of primary amines with tetramethylphenylguanidine and cyanophosphonates at −10 °C under an atmosphere of CO 2 furnishes cyanoformamides in good yields. 23 Dong and co-workers 24 employed phosphoryltrichloride (POCl 3 ) to convert 1-acyl-1-carbamoyl oximes to cyanoformamides, while concurrently Wu and co-workers 25 reported an eco-friendly method for the conversion of 2-oxoaldehydes into cyanoformamides using iodosobenzene diacetate (IBD) as oxidant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, other more direct synthetic methods have been developed (Scheme 2). 23–29 For instance, Muñoz reported that the reaction of primary amines with tetramethylphenylguanidine and cyanophosphonates at −10 °C under an atmosphere of CO 2 furnishes cyanoformamides in good yields. 23 Dong and co-workers 24 employed phosphoryltrichloride (POCl 3 ) to convert 1-acyl-1-carbamoyl oximes to cyanoformamides, while concurrently Wu and co-workers 25 reported an eco-friendly method for the conversion of 2-oxoaldehydes into cyanoformamides using iodosobenzene diacetate (IBD) as oxidant.…”
Section: Introductionmentioning
confidence: 99%
“… 26 At the same time, Schwartz's group described solvent-free access to secondary and tertiary cyanoformamides from TMSCN and carbamoyl imidazoles. 27 Recently, cyanoformamides were prepared from N , N -disubstituted aminomalononitriles 28 with CsF as the promoter and in another study, 4,5-dioxo-imidazolinium cation activation of 1-acyl-1-carbamoyl oximes was used. 29 Electrochemical synthesis of cyanoformamides was also reported starting from trichloroacetonitrile and secondary amines mediated by heptamethyl cobyrinate, a B 12 derivative.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and co‐workers (2019) reported an efficient method for synthesizing formamides [39] 63 by CsF‐promoted oxidative decyanation of 2‐dialkylamino malononitriles 62 (Scheme 33). An alternative finding for the preparation of cyano formamides was conventionally prepared from primary and secondary amines.…”
Section: α‐Aminonitriles To Amidesmentioning
confidence: 99%
“…Yet, the use of highly toxic and structurally complex reagents hampered their synthetic applications. Until recently, sporadic examples of alternative approaches to cyanoformamide formation were reported . Although effective, most of these protocols called for elevated temperatures (60–140 °C) ,− and long reaction times , or suffered from limited product scope excluding secondary cyanoformamides. ,, It is worthy of note that Dong and co-workers reported a new pathway for the synthesis of cyanoformamides from readily accessible 1-acyl-1-carbamoyl oximes mediated by phosphoryltrichloride (POCl 3 ) .…”
Section: Introductionmentioning
confidence: 99%